2021
DOI: 10.1088/1757-899x/1132/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization and Analysis of External Corrugation and Geometry of Asymmetrical Bellow Flexible Pneumatic Actuator

Abstract: Pneumatic soft actuators are a highly researched topic in soft robotics. The paper discusses the design and analysis of an Asymmetric Flexible Pneumatic bellow Actuator (AFPBA). This kind of actuator is cheap, easy to produce, reliable and durable. Soft grippers commonly use this actuator to pick fragile objects. The objective is to design an actuator which produced the maximum bending and study the effect of external corrugation and eccentricity on the actuator to select the optimal design. Optimum eccentrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…34 Multiobjective goals balancing bending angle and contact force have been targeted through integrated FEA and optimization. [35][36][37][38] Overall, these pioneering studies have established the utility of modeling and analysis techniques for improving soft actuator designs.…”
Section: Introductionmentioning
confidence: 99%
“…34 Multiobjective goals balancing bending angle and contact force have been targeted through integrated FEA and optimization. [35][36][37][38] Overall, these pioneering studies have established the utility of modeling and analysis techniques for improving soft actuator designs.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review on geometrical aspects of soft actuators it is observed that, comparatively fewer studies have investigated the semi-cylindrical shaped actuators [27][28][29][30]. Among these studies, Tan et al [28] and Wang et al [30] experimentally measured the forces generated by the soft gripppers.…”
Section: Introductionmentioning
confidence: 99%